2006
DOI: 10.1051/gse:2005028
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantitative trait loci affecting fatness and breast muscle weight in meat-type chicken lines divergently selected on abdominal fatness

Abstract: -Quantitative trait loci (QTL) for abdominal fatness and breast muscle weight were investigated in a three-generation design performed by inter-crossing two experimental meattype chicken lines that were divergently selected on abdominal fatness. A total of 585 F 2 male offspring from 5 F 1 sires and 38 F 1 dams were recorded at 8 weeks of age for live body, abdominal fat and breast muscle weights. One hundred-twenty nine microsatellite markers, evenly located throughout the genome and heterozygous for most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 12 publications
3
27
0
Order By: Relevance
“…A number of studies reported significant QTL effects in the 167–179 Mb region of GGA1. Uemoto et al also detected QTL affecting BW42 and BW63 in 165–172 Mb on GGA1 [11], and QTL effects were also reported in these regions were associated with BW28–BW84, average daily gain, WW or BMW [2], [6], [7], [10], [11], [15]. Besnier et al reported a QTL for BW56 in the 169–175 Mb region of GGA1 with the most significant QTL effect at position 173,709,609 bp on GGA1 [35].…”
Section: Discussionmentioning
confidence: 96%
“…A number of studies reported significant QTL effects in the 167–179 Mb region of GGA1. Uemoto et al also detected QTL affecting BW42 and BW63 in 165–172 Mb on GGA1 [11], and QTL effects were also reported in these regions were associated with BW28–BW84, average daily gain, WW or BMW [2], [6], [7], [10], [11], [15]. Besnier et al reported a QTL for BW56 in the 169–175 Mb region of GGA1 with the most significant QTL effect at position 173,709,609 bp on GGA1 [35].…”
Section: Discussionmentioning
confidence: 96%
“…Here we validated this EM correction with experimental data, which has seldom been achieved to date. Another approach to correct the overestimation of QTL contributions was proposed by Lagarrigue et al (2006) for QTL detected in chicken. It is based on the hypothesis of strict truncations of the normal distribution, i.e., a situation that was not adapted to our experimental conditions.…”
Section: Qtl Contributions To Phenotypic Variationmentioning
confidence: 99%
“…Although QTL mapping has been very successful in domestic animals for many complex quantitative traits and a few prominent findings have been reported [11], [12], [13], [14], identification of quantitative trait mutations (QTMs) is still a challenge due to the commonly existing limitations of linkage analysis [15]. Recently, the first high-density 60 K porcine SNP array has been developed [16], which offers the prerequisite of genome-wide association study (GWAS) in swine, a powerful approach for high-resolution mapping of loci controlling phenotypic traits.…”
Section: Introductionmentioning
confidence: 99%